Soft computing based on a selection index method with risk preferences under uncertainty: applications to construction industry. (2018) - Gitinavard, H.; Foroozesh, N.; Mousavi, S. Meysam; Mohagheghi, V.
Decision making in construction industry is a dynamic procedure which is concerned with choosing a reasonable strategy to accomplish the stated objectives. In this paper, a new developed hesitant fuzzy preference selection index (HFPSI) method in view of another soft computing approach with risk preferences of decision makers (DMs) is proposed to manage multi-criteria decision making (MCDM) issues in construction industry while applying hesitant fuzzy sets (HFSs) to represent the uncertain information under hesitant uncertainty. The proposed technique notwithstanding considering subjective surveying criteria, respects the DMs' troubles in deciding the membership of an element into a set. The proposed HFPSI approach is actualised by utilising two real case studies in the construction industry and the results are examined. The studied cases for the best construction project and the best contractor also demonstrate the effectiveness of applying the proposed method while considering a group of the DMs' ideas and hesitancy.